Manajemen Pengembangan Kurikulum Mata Pelajaran Seni Budaya melalui Metode PjBL di SMP Muhammadiyah 14 Surabaya - Aulia, Maya Zahra; Khumairo, Ayu Dwi Zam Zam; Aprilia, Marshanda; Wulandari, Rida (TSAQOFAH, 2024)
The curriculum is a set of subjects and educational programs provided by an educational institution that contains the design of lessons to be given to students. This article aims to discuss the management of Cultural Arts curriculum development using Project-based Learning (PjBL) method at SMP Muhammadiyah 14 Surabaya. The main objective of this research is to increase student engagement and effectiveness of Cultural Arts learning through innovative approaches. The curriculum management steps include student needs analysis, curriculum planning that integrates PjBL, selection of relevant art projects, development of teaching materials, teacher training, project implementation in daily learning, continuous evaluation, and parent and community involvement. By integrating PjBL, this research seeks to create a more dynamic and creative learning environment, hoping to improve students' understanding of cultural arts and enrich their learning experience. Periodic evaluation and updating is also the focus of this research to ensure suitability with students' needs and national curriculum development. The results of this research are expected to contribute to the development of more innovative and relevant learning methods in the field of Cultural Arts at SMP Muhammadiyah 14 Surabaya.